Association of iron deficiency with incident cardiovascular diseases and mortality in the general population. (5th October 2021) - Schrage, Benedikt; Rübsamen, Nicole; Ojeda, Francisco M.; Thorand, Barbara; Peters, Annette; Koenig, Wolfgang; Söderberg, Stefan; Söderberg, Maja; Mathiesen, Ellisiv B.; Njølstad, Inger; Kee, Frank; Linneberg, Allan; et al.
Abstract: Aims: Although absolute (AID) and functional iron deficiency (FID) are known risk factors for patients with cardiovascular (CV) disease, their relevance for the general population is unknown. The aim was to assess the association between AID/FID with incident CV disease and mortality in the general population. Methods and results: In 12 164 individuals from three European population‐based cohorts, AID was defined as ferritin < 100 μg/L or as ferritin < 30 μg/L (severe AID), and FID was defined as ferritin < 100 μg/L or ferritin 100–299 μg/L and transferrin saturation < 20%. The association between iron deficiency and incident coronary heart disease (CHD), CV mortality, and all‐cause mortality was evaluated by Cox regression models. Population attributable fraction (PAF) was estimated. Median age was 59 (45–68) years; 45.2% were male. AID, severe AID, and FID were prevalent in 60.0%, 16.4%, and 64.3% of individuals. AID was associated with CHD [hazard ratio (HR) 1.20, 95% confidence interval (CI) 1.04–1.39, P  = 0.01], but not with mortality. Severe AID was associated with all‐cause mortality (HR 1.28, 95% CI 1.12–1.46, P  < 0.01), but not with CV mortality/CHD. FID was associated with CHD (HR 1.24, 95% CI 1.07–1.43, P  < 0.01), CV mortality (HR 1.26, 95% CI 1.03–1.54, P  = 0.03), and all‐cause mortality (HR 1.12, 95% CI 1.01–1.24, P  = 0.03). Overall, 5.4% of all deaths, 11.7% of all CV deaths, and 10.7% of CHD were attributable to FID. Conclusions: In the general population, FID was highly prevalent, was associated with incident CHD, CV death, and all‐cause death, and had the highest PAF for these events, whereas AID was only associated with CHD and severe AID only with all‐cause mortality. This indicates that FID is a relevant risk factor for CV diseases in the general population.